Know Ye not that There Is a Prince and a Great Man Fallen This Day (2 Sam 3, 38): The Image of Jan Karol Chodkiewicz in Funeral Sermons and Orations - Vaitkevičiūtė, Viktorija (Senoji Lietuvos literatūra, 2024)
After the death of Jonas Karolis Chodkevičius (Jan Karol Chodkiewicz, c.1571–1621), a prominent politician and military leader of the Grand Duchy of Lithuania, eight printed funerary texts are known: five sermons in Polish and three speeches, two in Latin and one in Polish. These are the funeral sermons in Polish by Stanisław Rochowicz (b. 1636), a Jesuit preacher at the Chodkiewicz estate, Bonawentura Czarliński (b. 1648), a Bernardine; Jakub Hasius (b. 1648), a Jesuit, who later joined the Order of Penitential Canons; Melchior Stefanides (Stefański, Stefanowicz, c. 1565–1638), a theologian and the first rector of the Zamość Academy; Fabian Birkowski (1566–1636), a Polish Dominican and former chaplain of the Chotyn battle camp. The speeches were the following: ‘Mowa’ by Jakub Sobieski (1591–1646), a politician, a noble, the father of the future King John III Sobieski (1629–1696); ‘Oratio’ by Szymon Starowolski (1588–1656), a historian and Chodkiewicz’s secretary; ‘Oratio’ by an anonymous author, which was printed by the Baroque author Rafał Skorulski in the collection Laurus immortalitatis (The Laurel of Immortality) dedicated to Jan Karol Chodkiewicz together with paratheatrical emblems by other students of the Jesuit College in Nesvizh. After briefly presenting the circumstances of deliverance and publishing of the funeral sermons and speeches, the article seeks to find out to what extent the preachers sought to individualise Chodkiewicz or to refer to the details of his biography in discussing the outstanding and well-known Baroque warlord, or whether they presented a generalised model of a Christian, of a believer, based on the image of miles Christianus (Christian soldier) that had become popular in the Baroque period. These texts show an attempt to show a picture of a real person, describing, even if schematically, his appearance, enumerating his moral traits, and discovering details of his everyday life. Birkowski’s first-person speeches also add liveliness and verisimilitude to the portrayal of the warlord. Considering that only a small part of the nobility took part in battles at that time, Chodkiewicz’s personality was exceptional, which is evidenced by the numerous and detailed descriptions of battles in the sermons. Rarely do funeral sermons of the time devote as much space to descriptions of battles, despite the fact that they are usually dedicated to famous warlords. However, despite the individual qualities that seem to be unique to Chodkiewicz, the funeral sermons present an idealised image of a senator, a hetman, a military leader, which corresponds to the image of miles Christianus. The sermons present a certain type of a Catholic noble: a brave warrior knight who fights for his homeland and his faith, and personalised with regard of him being an extraordinary warlord. At the same time, the image of Chodkiewicz, like the heroes of other funeral sermons, serves as a role model for the society of the time in order to trigger the fading civic spirit and a sense of love of the homeland.